Eternity in Two Dimensions: When The Cycle of Destruction Encounters Qur’anic Harmony in Surah Al-Nisa’ (4:57) - Agus Fitrah Lianor; Gita Lupiana; Najamudin M. Lobang (BELIEF: Sociology of Religion Journal, 2026)
The eschatology of local religions and Islam differs fundamentally in their narratives of eternity. The difference is understood by Kaharingan as a reunion with ancestors who are constantly bound by the cycle of life, with the power of ceremonial synceitism playing a full role in its journey, and Islam offering, through doctrine, guidance that addresses different circumstances along its world journey. This writing accommodates the eternal linearity understood by both: conceptually, the initiation and the journey of the spirit are the same, given the existence of the spirit's place and its eternity. In addition, this article aims to examine the text of the Qur'an an-Nisa 4:57, which provides descriptive information for all mankind to receive God's Promise. Especially on the use of the double words "Khulud and Abadan". His finding that Abadan would not be separated from Khulud is a strong semantic affirmation. The analysis was carried out using stylistic studies of word structure and meaning to examine the intention to construct an image of heaven and to promise existence.